Growth and Development of Helicoverpa armigera (Lepidoptera: Noctuidae) Larvae Infected by Heliothis virescens ascovirus 3i (HvAV-3i) - Chen, Gong; Liu, Hang; Mo, Bo-Cheng; Hu, Jue; Liu, Shuang-Qing; Bustos-Segura, Carlos; Xue, Jing; Wang, Xing (Frontiers in Physiology, 2020)
Although the cotton bollworm Helicoverpa armigera has traditionally been controlled by application of chemical pesticides, chemical control selects for resistance, pollutes the environment, and endangers human health. New methods for controlling H. armigera are therefore needed. Heliothis virescens ascovirus 3i (HvAV-3i) is a recently identified virus of lepidopteran larvae. We tested the effects of HvAV-3i on H. armigera larvae following oral ingestion of HvAV-3i-containing hemolymph (about 1.0×1010 virus genome copies per larvae) and following injection of HvAV-3i-containing hemolymph by insertion of a needle. Following oral ingestion, first-instar to fifth-instar larvae grew and developed normally. Following needle injection, in contrast, the corrected mortality of third- and fourth- instars was 88.9 ± 2.1% and 93.7 ± 3.4%, respectively. Food intake was significantly lower for larvae injected with virus-containing hemolymph than with virus-free hemolymph. Larvae injected with virus-containing hemolymph had extended survival times and could not complete the pre-pupal stage. These results indicate that inoculation of HvAV-3i via needle injection but not via oral ingestion significantly reduced the growth and development of H. armigera larvae.